PENGARUH INVESTMENT OPPORTUNITY SET (IOS), UKURAN PERUSAHAANÂ DAN STRUKTUR MODAL TERHADAP KUALITAS LABA - DWI LESTARI, RETNO (Jurnal Akuntansi AKUNESA, 2017)
This study aims to determine the effect of investment opportunity set (IOS), firm size and capital structure to earnings quality. This research is quantitative method and uses sample of companies listed on Indonesia Stock Exchange for 2012 untill 2015. Using stratified sampling and simple random sampling methods, total samples are 297 companies. Investment opportunity set (IOS) is measured by capital expenditure to book value of assets; firm size is measured by total assets; capital structure is measured by leverage; and earning quality is measured by Earnings Response Coefficient. Using multiple linear regression analysis, the result shows that investment opportunity set (IOS), firm size and capital structure have no effect on earnings quality. Keywords: capital structure, earnings quality, firm size, investment opportunity set (IOS).